Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Wordwall Terhadap Pemahaman Konsep Pecahan Pada Siswa Kelas 3 SDN 88 Palembang - nia trianita; Allen Marga Retta; Arief Kuswidyanarko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall on students’ understanding of fraction concepts in grade III at SDN 88 Palembang. The research used a true experimental design with a pretest-posttest control group design. The sample was randomly selected: class III C as the experimental group and class III A as the control group, with 32 students in each class. The research instrument was a test of fraction concept understanding, given before and after the treatment. Data analysis using the t-test showed a significant difference between the posttest scores of the experimental and control groups. The experimental group obtained an average score of 81.59, while the control group scored 71.44. A significance value of 0.000 < 0.05 indicates that the PBL model assisted by Wordwall had a significant effect on improving students’ understanding of fraction concepts. Thus, it can be concluded that the PBL model assisted by Wordwall is effective in teaching fractions to enhance the conceptual understanding of grade III students at SDN 88 Palembang.